MEMAHAMI PEMBENTUKAN SIKAP (ATTITUDE) DALAM PENDIDIKAN DAN PELATIHAN - Ati Dahniar (Tatar Pasundan: Jurnal Diklat Keagamaan, 2019)
The purpose of this study is to explore some of the results of previous studies that show a positive relationship between training and employee competency improvement. The main question of this study is whether attitudes can be built through training? This study was conducted by looking for the meaning and finding important information about the competencies expected from a training activity. By drawing on the existing literature, not only topic under consideration is theorize, but also formulates and discusses the proposition that will help illuminate and discuss some ways for the firms to understand the effect of training on employees performance which include knowledge, skills and attitudes. The results of the study showed that temporary training in relation to improving attitude competencies was not the same with the same concept through an educational process that had a longer duration. So, the KSA conception in relation to training, "A" is not representing attitude, but abilities. Keywords: abilities; attitude; education; knowledge; skills; training